2015
DOI: 10.4238/2015.november.24.4
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance gene (MDR1) polymorphisms may not be directly associated with response to imatinib in chronic myeloid leukemia

Abstract: ABSTRACT. Our study aimed to investigate the association between multidrug resistance (MDR1) gene polymorphisms and the response to imatinib (IM) in chronic myeloid leukemia (CML). An electronic databases in PubMed, Cochrane Library, Wanfang, China National Knowledge Infrastructure, and VIP were searched using combinations of keywords relating to MDR1 polymorphisms and the response to IM in CML. Studies retrieved from database searches were screened using stringent inclusion and exclusion criteria. The Compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In 2015 Wang et al published a meta-analysis of 10 studies which involved 987 patients with CML and evaluated the significance of the polymorphisms rs1045642, rs1128503 and rs2032582 in ABCB1 (MDR1). The meta-analysis did not demonstrate an association between achieving optimal response and the genotypes of a certain polymorphism [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015 Wang et al published a meta-analysis of 10 studies which involved 987 patients with CML and evaluated the significance of the polymorphisms rs1045642, rs1128503 and rs2032582 in ABCB1 (MDR1). The meta-analysis did not demonstrate an association between achieving optimal response and the genotypes of a certain polymorphism [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis of Asian patients found that ABCB1 C1236T polymorphism was associated with increased risk of imatinib resistance while, no association was found with ABCB1G2677T or C3435T polymorphism with imatinib resistance [24]. In contrast to the aforementioned meta-analysis, meta-analysis by Wang et al [25] did not find any association of ABCB1 gene polymorphism with imatinib response. Another recent meta-analysis suggested that ABCB1 polymorphisms were not associated with MMR and complete molecular response (CMR) with use of imatinib [26].…”
Section: Effect Of Plasma Protein Binding Of Imatinib On Clinical Outcomementioning
confidence: 90%
“…It is one of the largest studies, across ethnicity, and genetic models; compared to previous meta-analysis. [22][23][24] Our meta-analysis was conducted in 653 cases and 757 controls; 796 cases and 971 controls and 630 cases and 687 controls for the C1236T, the C3435T and the G2677T/A; respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the association between MDR1 variants and IM response have been largely investigated and enrolled in meta-analysis. [22][23][24] Yet, the C1236T have been considered a potential marker mainly in Asian Population; 24 whereas; the 2677 G allele or 3435 T allele predicted a worse response to IM in CML patients. 23,24 The heterogeneity of previously results illustrates a possible role of ethnic differences in the genetic background.…”
Section: Discussionmentioning
confidence: 99%